Behavioral Heterogeneity in the US Sulfur Dioxide Emissions Allowance Trading Program - Olivier Rousse; Benoît Sévi (European Regional Science Association (ERSA), 2005)
At present, it is widely recognized that under the hypothesis of perfect market, a system of emission permits is a flexible instrument to attain an environmental objective at least aggregate cost. Unfortunately, perfect market assumptions rarely hold in practice. Indeed, emission permits markets can suffer of several impediments such as uncertainties, high transaction costs, market power, imperfect monitoring and enforcement. In this paper, we focus our attention on uncertainty. In a marketable permits market, firms may face various kind of uncertainty like permit price uncertainty, demand uncertainty that means production and emissions uncertainty, abatement costs uncertainty, and regulatory uncertainty. Assuming that the overall uncertainty is included in the permits price uncertainty (which is a reasonable assumption even if in previous contributions, other uncertainties were assumed to capture the whole risk ), we provide an analytical explanation of banking, using the concept of prudence developed by Kimball (1990). We show that prudence behaviour is a sufficient condition for the firm to save permits in portfolio (equivalent to a precautionary premium) and that the number of permits saved in portfolio decreases when interest rate increases. Results are not so far from previous literature and seem to indicate that uncertainty has disturbing effects on trading. Prudent behaviours of regulated firms lessen trade volumes in emissions permits markets and seem to indicate that possible welfare gains exist from governmental intervention (trading pro-actively in the emission permits market as mentioned by Baldursson and von der Fehr (2004) for instance). The more interesting point of the paper is the estimation of prudence provided using data from the US Acid Rain Program (Phase II, 2000-2004). To our knowledge, this is the first attempt to measure prudence in a production framework, compared to works estimating prudence in a consumption framework (Guiso, Jappelli, Terlizzese (1996), Lusardi (1997,1998), Parker (1999) among othersEisenhauer & Ventura (2003, 2004) and Halek & Eisenhauer (2001) may also be cited.) or using experimental data (Eisenhauer(2000) or Miyata (2003)). Particularly, trade level are put in perspective with the structure (utilities or not, number of units owned, total revenues,...) of the firm to assess if there is a form of corporate prudence. Corporate prudence is no more than a form of corporate hedging if we consider permits as forward contracts following Maeda & Tezuka(2004). Discriminant characteristics are also discussed.
Keywords: 330